Theoretical Raman and FTIR Vibrational Analysis of 2-Phenyl-1H-Indene-1,3(2H)-Dione by Ab Initio Method (Journal of Atomic and Molecular Sciences, 2021)
2-phenyl-1H-indene-1,3(2H)-dione is an anticoagulant and functions as a Vitamin K antagonist. The equilibrium geometries and harmonic frequencies of the molecule under investigation was determined and analyzed at DFT level employing the basis set 6-311++G($d,p$). The skeleton of the optimized molecules is found to be non-planar. The plane of the phenyl ring and the mid-plane of the bicyclic moiety are almost perpendicular to each other. In general, a good agreement between experimental and calculated normal modes has been observed. A comparison of calculated frontier orbital energy gap 2-phenyl-1H-indene-1,3(2H)-dione and 1H-indene-1,3(2H)-dione shows that the 2-phenyl-1H-indene-1,3(2H)-dione is slightly more reactive molecule than  its parent. The other molecular properties of 2-phenyl-1H-indene-1,3(2H)-dione like dipole moment, polarizability, MESP potential surface have also been calculated and compared with the parent molecule.